Dynamic coordinated maintenance of wind-farms with risk-averse agents under CVaR criterion. (December 2022) - Ramirez, Stefanny; Bauso, Dario
Abstract: We study a coordinated maintenance problem for multi-turbine offshore wind-farms. The deterioration of the turbines follows a Poisson process and the optimal order quantity for a single wind-farm, as well as for a coalition of wind-farms, is obtained using the analogy with the risk-averse newsvendor model considering the conditional value at risk (CVaR) criterion. We apply the theory of robust dynamic coalitional games to design a stable allocation mechanism that distributes the cost of the coalition among all the participants in a fair and stable way.